2016
DOI: 10.1158/1078-0432.ccr-15-1008
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Circulating Tumor Cells Are Associated with Response and Survival Following Treatment of Metastatic Neuroendocrine Neoplasms

Abstract: Purpose: To investigate posttreatment circulating tumor cell (CTC) counts in patients with neuroendocrine neoplasms (NENs) as a predictive biomarker for disease progression and overall survival (OS).Experimental Design: Patients with metastatic NENs commencing therapy were prospectively recruited (n ¼ 138). Blood samples were obtained for evaluation of CTCs using the CellSearch platform and for chromogranin A (CgA) at baseline, three to five (median, 4.3) weeks and 10 to 15 (median 13.7) weeks after commencing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 28 publications
2
55
0
Order By: Relevance
“…Current strategies to analyze tumor genomes are limited by the need of sufficient amount of good quality tumor tissue. In the future peripheral blood samples (liquid biopsies) containing either circulating tumor cells or circulating cell free DNA might instead be used for recognition of the genomic landscape of the individual tumors (168,169).…”
Section: Authors Perspectives and Future Implicationsmentioning
confidence: 99%
“…Current strategies to analyze tumor genomes are limited by the need of sufficient amount of good quality tumor tissue. In the future peripheral blood samples (liquid biopsies) containing either circulating tumor cells or circulating cell free DNA might instead be used for recognition of the genomic landscape of the individual tumors (168,169).…”
Section: Authors Perspectives and Future Implicationsmentioning
confidence: 99%
“…Improved methods of patient stratification are therefore required in neuroendocrine tumours in order to provide benefit for those who will respond and spare toxicity in those who will not. There is considerable interest in the predictive role of circulating biomarkers, including NETspecific multi-gene transcripts (NET-test) (Modlin et al 2014), cfDNA and CTCs (Khan et al 2016), but further work is required to prospectively validate these markers before they can be used to select patients for chemotherapy (Modlin et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…• Significant association (P < 0.001) between the first post-treatment (after 3-5 weeks) CTCs count and progressive disease (PD): PD in 8% of patients with 'favorable count' (0 CTCs at baseline and after treatment, or ≥50% CTCs reduction after treatment) vs 60% in unfavorable group (<50% CTCs reduction or increase) • Changes in CTCs count at the first post-treatment time (after 3-5 weeks) strongly associated with OS (P < 0.001): the best outcome in group with 0 CTCs count at baseline, followed by the group with ≥50% CTCs reduction after treatment (HRs = 3.31; 95% CI = 1.50-7.32) and then the group with <50% CTCs reduction or increase (HRs = 5.07; 95% CI = 2.48-10.38) • In multivariate analysis changes from baseline CTCs count (P = 0.0002) and grade (P = 0.0046) resulted independent prognostic factors Khan et al (2016) 34 Merkel cell carcinomas • Correlation between CTCs positivity (≥1 CTCs) and extent of disease (P = 0.004) • Statistically significant difference in median OS between CTCs positive and CTCs negative samples (P = 0.0003), also in case of regional node metastases (P = 0.015) Blom et al (2014) 30 Merkel cell carcinomas • Significantly higher CTCs count in patients with active disease • Increasing CTCs count associated with development of new metastases Gaiser et al (2015) 59 Small cell lung cancers • Association between CTCs count <2 and prolonged OS and PFS (P ≤ 0.001)…”
Section: Part 2 Micrornasmentioning
confidence: 99%
“…In addition, the study showed that patients with more than one CTC displayed worse PFS and OS as compared to patients with <1 CTC, independently of other prognostic markers. To clarify whether CTCs may also predict the response to treatment, the same authors (Khan et al 2016) evaluated CTC count before and after treatment in 138 metastatic NEN patients (31 pNEN including 9 G1, 7 G2 and 15 G3; 81 midgut NENs including 48 G1, 28 G2 and 5 G3; 12 lung NENs including 4 G1, 6 G2 and 3 G3) and found that first post-treatment CTC count was significantly associated with progressive disease. Indeed, a better outcome was recorded in patients that did not have CTCs before and after therapy and in patients displaying a >50% reduction in CTC count after treatment.…”
Section: :6mentioning
confidence: 99%